Adverbial clauses and adverbial concord - Endo, Yoshido; Haegeman, Liliane (Glossa (London), 2019)
This paper speculates that the merge site of an adverbial clause, i.e. its external syntax, is determined by its derivational history, i.e. its internal syntax. Starting from the distinction between central adverbial clauses and peripheral adverbial clauses, it is first shown that the degree of integration of an adverbial clause correlates with its internal syntax, i.e. the availability of left peripheral functional material. The correlation can be informally stated as follows “the more structure is manifested in the adverbial clause, the higher it is merged”. This paper develops a derivational account for this correlation. The proposal adopts the movement derivation of adverbial clauses, according to which, like relative clauses, adverbial clauses are derived by movement of a specialized IP-related operator (aspectual, temporal, modal, etc) to the left periphery. The paper explores observations drawn from the traditional literature on Japanese grammar (Minami 1974; Noda 1989; 2002) to the effect that the amount of TP-internal functional structure in an adverbial clause also correlates with the presence of specialized functional particles in the matrix clause with which the clause merges. Specifically, we explore Japanese data discussed in Endo (2011; 2012). It is proposed that the merger of an adverbial clause with the associated main clause is determined by the label of the adverbial clause, itself the result of the movement derivation.